2016
DOI: 10.1007/s11356-016-6444-4
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic gasification of biomass (Miscanthus) enhanced by CO2 sorption

Abstract: The main objective of this work concerns the coupling of biomass gasification reaction and CO sorption. The study shows the feasibility to promote biomass steam gasification in a dense fluidized bed reactor with CO sorption to enhance tar removal and hydrogen production. It also proves the efficiency of CaO-CaAlO/olivine bi-functional materials to reduce heavy tar production. Experiments have been carried out in a fluidized bed gasifier using steam as the fluidizing medium to improve hydrogen production. Bed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…at temperatures higher than 727 and 675°C, respectively. Moreover, Zamboni et al . and Aarlien et al .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…at temperatures higher than 727 and 675°C, respectively. Moreover, Zamboni et al . and Aarlien et al .…”
Section: Resultsmentioning
confidence: 98%
“…This increase clearly shows the existence of reverse carbonation (calcination reaction) in the system, which has been reported by Xu et al 15 and Pfeifer et al 16 at temperatures higher than 727 and 675 °C, respectively. Moreover, Zamboni et al 17 and Aarlien et al 18 reported maximum CO 2 sorption temperatures at 660 and 700 °C for enhanced H 2 production, respectively. This suggests that the optimum temperature of 675 °C is suitable for high H 2 composition with minimal CO 2 in ICA steam gasification, and also provides evidence of a good fluidized bed operation in the present study.…”
Section: Presence Of Moisture In Gas-analysing Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…[1,2] Through ag asificationp rocesst hat involves as eries of thermochemical conversion reactions,b iomass solids can be converted to gas-phasep roducts.T he gas/vapor-phase end productso fb iomass gasification are composed mainlyo fC O, CO 2 ,C H 4 ,H 2 ,a nd low concentrations of C 2 -C 3 species. [3,4] Thec oncentration of H 2 in syngas produced from the gasification of biomass is usuallyl ow,b ut can be increased by the followingr eactions that produce additional H 2 :…”
Section: Introductionmentioning
confidence: 99%
“…They show that adding 10 mol% Li 2 CO 3 promotes both sorption and desorption due to a K-Li eutectic phase that promotes the diffusion of K and CO 2 into the sorbent matrix. Second, Zamboni et al (Zamboni et al 2016) demonstrate the synergistic effect of high-temperature sorption on steam-based biomass gasification in a fluidized bed of CaOCa 12 Al 14 O 33 /Olivine to enhance hydrogen production and tar removal.…”
mentioning
confidence: 99%